Let \(f\), \(g\), and \(h\) be polynomials such that \( h(x) = f(x)\cdot g(x)\). If the constant term of f(x) is -4 and the constant term of h(x) is 3, what is g(0)?

Guest Apr 20, 2021

#1**+1 **

we only have to find the constant of g for this problem:

-4$\cdot$c=3

c=-3/4

therefore, g(0) = 0x^2+0x-3/4=$\boxed{-\dfrac34}$

SparklingWater2 Apr 20, 2021

#1**+1 **

Best Answer

we only have to find the constant of g for this problem:

-4$\cdot$c=3

c=-3/4

therefore, g(0) = 0x^2+0x-3/4=$\boxed{-\dfrac34}$

SparklingWater2 Apr 20, 2021